Safety and early effectiveness of robot‐assisted partial nephrectomy for large angiomyolipomas. (12th January 2017) - Golan, Shay; Johnson, Scott C.; Maurice, Matthew J.; Kaouk, Jihad H.; Lai, Weil R.; Lee, Benjamin R.; Kheyfets, Steven V.; Sundaram, Chandru P.; Cahn, David B.; Uzzo, Robert G.; Shalhav, Arieh L.
Abstract : Objective: To evaluate a multicentre series of robot‐assisted partial nephrectomy (RAPN) performed for the treatment of large angiomyolipomas (AMLs). Patients and Methods: Between 2005 and 2016, 40 patients with large or symptomatic AMLs underwent RAPN at five academic centres in the USA. Patient demographics, AML characteristics, operative and postoperative clinical outcomes were recorded and analysed. Surgical outcomes were compared between patients who underwent selective arterial embolisation (SAE) before RAPN and patients who did not undergo pre‐RAPN SAE. Results: The median (interquartile range [IQR]) tumour diameter was 7.2 (5–8.5) cm, and the median (IQR) nephrometry score was 9 (7–10). Six patients (15%) had a history of tuberous sclerosis and 11 (28%) had previously undergone SAE. The median (IQR) operative time and warm ischaemia time was 207 (180–231) and 22.5 (16–28) min, respectively. A non‐clamping technique was used in eight (20%) patients. The median (IQR) estimated blood loss was 200 (100–245) mL, and four patients (10%) received blood transfusion postoperatively. One intraoperative complication occurred (2.5%), and seven postoperative complications occurred in six patients (15%). During a median (IQR) follow‐up of 8 (1–15) months, none of the patients developed AML‐related symptoms. The median estimated glomerular filtration rate preservation rate was 95%. There were no differences in operative or perioperative outcomes between patients who underwent SAE before RAPN and those who did not. Conclusions: Robot‐assisted partial nephrectomy appears to be a safe primary or secondary (post‐SAE) treatment for large AMLs, with a favourable perioperative morbidity profile and excellent functional preservation. Longer follow‐up is required to fully evaluate therapeutic efficacy.